Copper isotopes as possible neoplasia biomarkers in captive wild felids. Issue 4 (29th June 2019) - Gourlan, Alexandra T.; Douay, Guillaume; Telouk, Philippe
Abstract: The longevity of zoo animals is increasing due to continuous improvement in husbandry and veterinary medicine. However, increasing age is correlated to a higher prevalence of neoplasia. Despite tremendous improvement in diagnoses and monitoring capacities, cancers are still a challenge for veterinarians within the global zoo community. The recent use of copper isotopes as biomarkers for neoplasia in both human and veterinary medicine is a promising and cost‐effective diagnostic tool. Two hundred and twenty‐nine serum samples from 10 different species of wild felids under human care were processed through mass spectrometry to determine the ratio of heavy and light copper isotopes ( 65 Cu/ 63 Cu). The results of this preliminary study exhibit an important variability between felid species, with a ratio ranging between −1.71 and 0.63. Additionally, copper isotopes seem to be a promising diagnostic tool in monitoring cancer in wild animals, as in human medicine, where the isotopic ratio decreases significantly with time in the presence of a tumor. Abstract : Evolution of δ65Cu in serum over time for feline diagnosed with cancer. Research Highlights: Neoplasia is associated with a modification of the isotopic 65 Cu and 63 Cu (∂Cu) ratio in blood. Therefore ∂Cu is considered as a biomarker of neoplasia in human and vet medicine. This study assessed the relevance of this biomarker in wild felids, by measuring the ∂Cu in 229 serum from ten captive felid species. In healthy animals, ∂Cu exhibited a high variability between species but was not influenced by gender or age. Also, ∂Cu is stable through time in healthy animals. As described in humans and dogs studies, the 25 samples from felids diagnosed with neoplasia, exhibited a lower ∂Cu compared to healthy animals, and the ratio decreased throughout time. The results from this pilot study highlight the promising interest in blood ∂ 65 Cu measurement in wild felids as a neoplasia biomarker. As such, this diagnostic test could be part of the annual health screenings of captive wild felids.